3PC-029 Management of a chemotherapy production after a cyber-attack in a public hospital. Issue 1 (23rd March 2023) - Muhammad, S; Gaspéri, E; Bordet, F; Maëstroni, ML
Abstract : Background and Importance: In August 2022, our hospital was victim of a massive cyber-attack. Every software, network and connected items were unusable including CHIMIO® which manages production of chemotherapy from prescription to administration. Our Chemotherapy Production Unit (CPU) usually produces about 19, 000 sterile preparations a year. Aim and Objectives: The objective was to pursue the production of chemotherapy respecting in maximum the usual production and quality process. Material and Methods: The first 3 days prescriptions were already validated and printed at the pharmacy, serving as: patient history, prescription and protocol model. A molecule data register was created on Excel® listing cytotoxic drugs data (stability, concentration…). First, Manufacturing Sheets (MS) were totally handwritten then an Excel® MS was developed, mimicking CHIMIO®. At first, a single model using copy-paste for labels was developed. Then, several models for bags, syringes or infusers were created, using formulas to automatically fill the labels, to secure and speed up the process. A scheduler traced all preparations by a unique number. Finally, a patient's history register was created with data needed for pharmaceutical validation. A second pharmacist double-checked every MS. Results: 437 preparations were made in degraded mode during 6 days (73/day). Only 5% of the production was outsourced in other hospitals. The first 5 MS were handwritten. Printing every MS with the first version of Excel® MS took about 3h/day. Then, improving Excel MS reduced edition and double-checking time to about 1h/day. Double-checking MS detected most of editing errors. During final checking of preparations, 3 errors (<1%) were detected. Two majors with wrong patient's name and dose (-47%) and one minor with wrong scheduler number. The recovery of CHIMIO® database was effective after 6 days. Transcription in CHIMIO® found only one undetected prescription error. Conclusion and Relevance: Development of a semi-automated Excel® tool and double control of MS has allowed us to maintain a safe and almost normal production. Excel® tool tracing patients history permits to detect prescriptions errors (dose adjustment, intervals of administration, protocols respect). Regular backups and development of a degraded mode protocol will be undertaken soon. References and/or Acknowledgements: Conflict of Interest: No conflict of interest